Contemporary Issues Related to Madrasah Ibtidaiyah Education - Lilla Septiliana; Ibnu Alwan Saputra (PGMI, STAI Miftahul Ula Nganjuk, 2025)
Education in Madrasah Ibtidaiyah faces the challenge of maintaining its identity as an early educational institution that instills religious teachings. Issues related to learning practices must be addressed comprehensively, as madrasahs are Islamic educational institutions with an important mission to educate the younger Muslim generation to become agents of social and national development toward a better future. This study aims to describe contemporary issues related to Ilmu Ke-Madrasah Ibtidaiyah (the science of Islamic elementary education). The discussion provides an overview of various issues and topics discussed within the global context of Madrasah Ibtidaiyah education. This research falls under the category of library research and also employs a qualitative approach. The results of the study reveal an overview of the Madrasah Ibtidaiyah (MI) prototype, as well as insights into the current issues occurring within the educational context of contemporary classrooms.